Identifying risk factors associated with juvenile offenders’ recidivism in India: a theoretical understanding - Pegu, Chandini (Humanities, Arts and Social Sciences Studies, 2021)
Juvenile offenders’ recidivism is considerably a less recognised topic in India. However, it is recently emerging as a major challenge for the Indian juvenile justice system and the society in general. Identifying the risk factors that facilitates recidivism among juveniles can better address the problem through incorporating successful rehabilitative measures. Intervening with the problem of juvenile recidivism is also important for the reason that the anti-social behaviour of juveniles does not persist throughout adulthood. The efficacy of the correctional programs undertaken in different correctional agencies and institutions for the offenders can also be identified while intervening into the problem. Prior research also shows that juvenile delinquents if not intervene effectively, later turns into adult hardened criminals. Therefore, to address the growing rate of adult criminal activity, the juvenile criminal activity needs to be prevented. Thus, the purpose of this study is to identify the major risk factors responsible for reentry of juveniles into juvenile institutions and intervene in order to help combat juvenile offenders’ recidivism. The study found that better rehabilitation programs designed for juvenile offenders reduce the recidivism rate. The paper is descriptive in nature and relies on secondary sources of data. This study would lead to the understanding of the background variables for the reason of juvenile offenders’ recidivism in India. It will also be useful for preventing juvenile offenders’ recidivism in the country and will consequently serve as a way of updating the literature on the topic.